Inhibitory effect of PXR on ammonia-induced hepatocyte autophagy via P53. (1st October 2018) - Yan, Linlin; Chen, Zhanfei; Wu, Luxi; Su, Yongfa; Wang, Xiaoqian; Tang, Nanhong
Highlights: PXR interferes with ammonia-induced hepatocyte autophagy. PXR inhibits ammonia-induced AMPKβ1 accumulation and activation. P53 binds to the AMPKβ1 promoter (−253 to −19) and transactivates its expression. Interaction of PXR and P53 affects AMPKβ1 expression. Abstract: Pregnane X Receptor (PXR), a nuclear receptor transcription factor, participates in a wide range of physiological activities, but the regulation of ammonia-induced hepatocyte autophagy by PXR is not yet clear. In this study, the levels of down-regulated LC3B-II and up-regulated SQSTM1 were found in ammonia-induced PXR-overexpressing (PXR+) liver cells, but the opposite appeared in PXR-knockdown (PXR−) liver cells. Rifampicin, a PXR-activating agent, elicits a similar effect as PXR+ cells. The mechanism analysis reveals that the levels of the energy-sensitive molecule AMPKβ1 and phosphorylated AMPKβ1 (p-AMPKβ1) in PXR− cells are higher than those in control cells, whereas the levels of this molecule in PXR+ cells are lower than those in control cells. Two active sites that bind to P53 exist in −253 to −19 at the promoter region of AMPKβ1, and their mutation can reduce the transactivating effect of AMPKβ1 that P53 relies on. A protein interaction also exists between PXR and P53. These findings indicate that PXR is a factor interfering the formation of ammonia-induced hepatocyte autophagy, and its inhibitory effect is achieved when P53 downregulates the expression and activity of AMPKβ1. This conclusion provides an appropriate clinical explanation for hepatotoxicity caused by the inhibitory effect of PXR-activating agent on hepatocyte autophagy.